Perancangan Digitalisasi Bimbingan Skripsi Jurusan Managemen Di Kampus F STIE Insan Pembangunan Berbasis Android - Ramadhan, Dani; Komalasari, Nia; Sofyan, Asep Abdul (Universitas Islam Syekh Yusuf Tangerang, 2024)
Science and technology continues to develop in line with the changing times that enter the digital era. This affects all aspects of life, including education. Starting from the Covid-19 situation, the entire teaching and learning process from the PAUD level to the university level changed the method to an online system. However, in the incident in the field, there are several agencies that still use conventional methods. As in the STIE Insan Pembangunan Campus, the thesis guidance process is still done face-to-face. This is considered less effective and seems to waste a lot of time. Therefore we need an information system in the form of a computerized thesis guidance application based on Android to facilitate the guidance process. The method used in this research is User Centered Design (UCD) which places the client as the center of a system development process. Based on the results of the author's research, the application built makes it easier for students and lecturers to conduct thesis guidance and this system is efficient so that the guidance process can run conducively according to schedule. The author gives several suggestions, one of which is that the application must be integrated by the campus so that the management of the accounts contained in this system becomes easier and there is no data aberration.